Lethal and behavioral effects of pesticides on the insect predator Macrolophus pygmaeus - Martinou, Angeliki F.; Seraphides, Nicos A.; Stavrinides, Menelaos (My University, 2014)
Macrolophus pygmaeus (Hemiptera: Miridae) is a common generalist predator in Mediterranean agro-ecosystems. We evaluated the lethal effects of six insecticides and a fungicide on M. pygmaeus nymphs exposed to the pesticides through three routes of exposure: direct, residual and oral. Chlorantraniliprole and emamectin-benzoate caused less than 25% mortality to M. pygmaeus and were classified as harmless according to the International Organization for Biological Control rating scheme. In contrast, thiacloprid and metaflumizone caused 100% and 80% mortality, respectively, and were classified as harmful. Indoxacarb and spinosad resulted in close to 30% mortality to the predator, and were classified as slightly harmful, while the fungicide copper hydroxide caused 58% mortality and was rated as moderately harmful. Chlorantraniliprole and thiacloprid were selected for further sublethal testing by exposing M. pygmaeus to two routes of pesticide intake: pesticide residues and feeding on sprayed food. Thiacloprid led to an increase in resting and preening time of the predator, and a decrease in plant feeding. Chlorantraniliprole resulted in a decrease in plant feeding, but no other behaviors were affected. In addition, thiacloprid significantly reduced the predation rate of M. pygmaeus, whereas chlorantraniliprole had no significant effect on predation rate. The results of the study suggest that thiacloprid is not compatible with M. pygmaeus, while further research needs to be carried out for metaflumizone and copper hydroxide. All other products seem to be relatively compatible with M. pygmaeus, though studies on their sublethal effects will shed more light into their safety.
Keywords: Conservation biological control; Mirid predator; Time allocation; Toxicity